Successful treatment of atrial flutter by repeated intraperitoneal and intra-amniotic injections of amiodarone in a fetus with hydrops - Pei-Hsuan Lin; Hsin-Hung Wu; Horng-Der Tsai; Charles Tsung-Che Hsieh (Elsevier, 2016)
Objective: We report a case of nonimmune hydrops fetalis caused by atrial flutter, which was successfully treated by intraperitoneal and intra-amniotic injections of amiodarone. Case Report: A 27-year-old woman presented at 30 weeks of pregnancy with hydrops fetalis caused by a fetal atrial flutter. As the transplacental passage of antiarrhythmic agents is impaired in hydrops fetalis, we chose direct treatment using fetal intraperitoneal and intra-amniotic injections (75-300 mg) of amiodarone. We managed to successfully convert the fetal atrial flutter to normal sinus rhythm. The woman delivered a live female baby at 33 weeks of gestation with normal sinus rhythm and neurological development. Conclusion: Intrauterine antiarrhythmic treatment can reduce perinatal morbidity and mortality. This report suggests that direct fetal therapy using intraperitoneal or intra-amniotic injections of amiodarone constitutes an effective treatment for atrial flutter in cases of hydrops fetalis.